Iot Based Smart Door Lock System - Sowmya, G; Divya Jyothi, G; Shirisha, N; Navya, K; Padmaja, B (International Journal of Engineering and Technology, 2018)
These days’ people are sky rocketing in technological advancements. This ushered to a lifestyle that’s become a child’s play. We are in pursuit of emerged advanced technologies and software with every single passing day. In the huge efforts of making our lives simpler and better we are contributing a fraction of a part through our project – SMART DOORS. Smart doors are a simple project that assists people in gaining the control to access the doors. Smart doors project prevents the entry of unauthorized personnel. This uses a simple Arduino board with a few lines of code dumped in it, a hexadecimal keypad and some jumper wires. The predominant attribute of this project is the Arduino board that facilitates the usage of this project. With this it is ready to be set up anywhere and everywhere with utmost expedite efforts. This prevents security breaches and helps establish a secure environment in and around.